From Recovery To Resilience : Global Strategies For Sustainable Economic Transformation In Northern Sri Lanka - Diya, D.; Kushi, N.J. (The Department of Law, Faculty of Arts, University of Jaffna / Surana and Surana International Attorneys India, 2025)
This study explores the interface of environmental sustainability and economic transformation in Northern Sri Lanka, its challenges, and strategies relative to similar situations in other countries. The region, coming out of decades of conflict, faces different challenges toward sustainability that are worsened by climate change, resource depletion, and socio-economic inequalities. Economic transformation in Northern Sri Lanka is crucial in order for sustainable development to materialize in a process in which the expansion of industries will have to be balanced against renewable energy and the environment. The study uses a comparative analytical framework, drawing analogies from countries such as Vietnam, Rwanda, or Bangladesh, which have become successful in transitioning to sustainable economic models in similar post-conflict or resource-poor contexts. This study is enhanced by primary data gathered by interviewing stakeholders and secondary materials composed of policy documents and environmental impact assessments. Northern Sri Lanka's environmental laws, including the National Environmental Act (NEA) and the Fauna and Flora Protection Ordinance (FFPO), safeguard ecosystems and promote sustainable development. Enforced by the Central Environmental Authority (CEA), these regulations balance ecological preservation with developmental needs, fostering regional sustainability and resilience. The findings indicate that in Northern Sri Lanka, the sectors of renewable energy and eco-tourism have experienced significant growth, but the lack of policy coherence and investment in green technologies still prevails. The lessons learned from comparable countries highlight the importance of having robust governance structures, integrated environmental policies, and grassroots mobilization. Moreover, the study identifies the need for targeted approaches that integrate traditional knowledge with modern sustainable practices. By overcoming these problems, Northern Sri Lanka can create an ideal model of sustainable transformation of economy that integrates ecological need with socio-economic development.
Keywords: Environmental sustainability; Economic transformation; Post-conflict challenges; Resource depletion; Environment impact assessment